INVESTIGATING CONTENT-BASED READING INSTRUCTION IN PROMOTING STUDENTS’ READING COMPREHENSION: A CLASSROOM ACTION RESEARCH - Khusniyah, Nurul Lailatul; Wadi, Ari Safar (Research And Innovation In Language Learning (RILL), 2020)
This study aimed at describing how content-based reading instruction on students? reading comprehension. The method used in this current research was a classroom action research. The participants were taken from an EFL classroom of a private madrasah in Narmada. Process of collecting data was taken using test and observation. Teacher and students? worksheets were the qualitative data collection instrument to assess the reading instruction process. Meanwhile, the test used TOEFL to measure students? reading comprehension. The research findings show that reading instruction achieved 71.42% in Cycle I  and 94.46% in Cycle II. The students? learning outcome shows 38.89% (Cycle I), and 83.34% (Cycle II). It means that there is a significant improvement of the reading comprehension from cycle I to cycle II. In addition, the students were active, enthusiastic, and participated in reading instruction using CBI.